KEARIFAN LOKAL KOMUNITAS PENANGKAP IKAN RUMAH LANTING DI DANAU MARE - Yuliana Yuliana (Prodi Sosiologi FISIP UPR, 2021)
This paper describes one of the local wisdoms of the lanting house fishing community in Lake Mare, in the form of environmentally friendly fishing gear, and tries to describe the problem of the lanting house wisdom left from the perspective of materialist social change. The research method uses descriptive qualitative. Data collection techniques are observation and interviews. Data analysis using the Miles and Huberman model includes reduction, data presentation, and drawing conclusions. The results showed that there are several tools and methods of catching fish that are environmentally friendly, including: lunta, tambak, pasat, rengge, buwu, rempa and banjur. Meanwhile, local wisdom is now competing with fish catching tools that are technological (time efficiency and yield), but are not environmentally friendly, this is one of the factors the lanting house is abandoned.